2021
DOI: 10.3390/plants10040803
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Profile Variation of Essential Oil from Dried Makwhaen Fruit and Related Species

Abstract: The aim of this research is to evaluate the relationship between genotype, phenotype, and chemical profiles of essential oil obtained from available Zanthoxylum spp. Three specimens of makhwaen (MK) distributed in Northern Thailand were genetically and morphologically compared with other Zanthoxylum spices, known locally as huajiao (HJ) and makwoung (MKO), respectively. HJ was taxonomically confirmed as Z. armatum while MKO and MK were identified as Z. rhetsa and Z. myriacanthum. Genetic sequencing distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…They indicated that the predominant components in the essential oil were limonene (62.51%) and sabinene (13.83%). In addition, the research conducted by Supabphol and Tangjitjaroenkun [30], as well as Sriwichai et al [31], reported that limonene and sabinene were major components of the essential oil extracted from Z. myriacanthum.…”
Section: Gc-ms Chemical Compositionsmentioning
confidence: 97%
“…They indicated that the predominant components in the essential oil were limonene (62.51%) and sabinene (13.83%). In addition, the research conducted by Supabphol and Tangjitjaroenkun [30], as well as Sriwichai et al [31], reported that limonene and sabinene were major components of the essential oil extracted from Z. myriacanthum.…”
Section: Gc-ms Chemical Compositionsmentioning
confidence: 97%
“…Sriwichai et al (2021) [ 5 ] published a research paper entitled “Aromatic Profile Variation of Essential Oil from Dried Makwhaen Fruit and Related Species”. This work was carried out to evaluate the relationships between the genotype, phenotype, and chemical profiles of essential oil obtained from Zanthoxylum spp.…”
Section: Overview Of the Special Issuementioning
confidence: 99%
“…Each dried plant material (100 g) was extracted by the hydro-distillation method using a Clevenger-type apparatus for 4 h [33]. The oils were dried over anhydrous sodium sulfate and filtrated through Whatman No.1 filter paper.…”
Section: Essential Oil Extractionmentioning
confidence: 99%